Private Sector Involvement in Tuberculosis Control in An Urban City of Western India- A Cross-Sectional Study - Khushboo Hadiya; Rahul Damor; Hiteshree Patel; Mohamed Anas Mohamed Faruk Patni; Kavita Bodar; JK Kosambiya (Medsci Publications, 2024)
Background: In India, TB diagnosis and treatment practices among Private Practitioners (PPs) vary widely and are not properly regulated by the national TB program. Despite their irrational and inequitable practises, PPs remain an important and preferred primary care provider for many people. The study was done to with the objectives to describe different diagnosis and treatment practices of Tuberculosis among private practitioners and their involvement in National Tuberculosis Elimination Program (NTEP). Material and Methods: A cross sectional study was performed among 303 PPs during October 2020 to March 2021 by using stratified random sampling to select private practitioners based on their speciality. Results: Most preferred investigation was Chest X ray (45.2%) followed by sputum smear microscopy (29.7%). Only 71.3% PPs practiced the correct regimen for new cases of Pulmonary TB according to NTEP. More than half of the PPs had TB training (59.7%). Majority of the PPs (90.1%) were involved in NTEP mainly by referral of TB patients to local government centres for treatment purpose. Conclusion: Preferred investigation for diagnosis of pulmonary TB was chest X-ray followed by sputum examination among PPs. The treatment regimen and duration of treatment varies among PPs as per their clinical judgement and practice.